The many-rooted earthball—Scleroderma geaster and S. polyrhizum revisited, with the description of a new species - Ortiz-Rivero, Javier; Watling, Roy; Guzmán-Dávalos, Laura; Martín, María P. (Phytotaxa, 2021)
Scleroderma (Order Boletales, Basidiomycota) species have a worldwide distribution. In this study, we review the Scleroderma polyrhizum/S. geaster complex. Eighty-two specimens from different geographic origins were analysed using morphological, mainly basidiospore size and ornamentation, and molecular characters (ITS nrDNA). Our results showed a clear separation of the specimens into four clades and each clade could be distinguished with morphological characters. Thus, European specimens grouped into two clades with those considered to be S. geaster distinct from those considered S. polyrhizum. Many specimens from the USA under the name S. polyrhizum correspond to S. texense or to a new species, here described as S. guzmanii. This study demonstrated the importance of the molecular DNA barcode ITS in genetic analyses to reveal and identify cryptic species in fungal morphospecies.